Osteocyte Apoptosis Contributes to Cold Exposure-induced Bone Loss - Du, Jingke; He, Zihao; Cui, Junqi; Li, Hanjun; Xu, Mingming; Zhang, Shuhong; Zhang, Shuangyan; Yan, Mengning; Qu, Xinhua; Yu, Zhifeng (Frontiers in Bioengineering and Biotechnology, 2021)
Emerging evidence indicates that bone mass is regulated by systemic energy balance. Temperature variations have profound effects on energy metabolism in animals. Multiple studies have shown that mild cold exposure can reduce bone mass by affecting bone remodeling. However, the in-depth mechanism behind this phenomenon remains unclear. Therefore, to address this issue, we exposed 2-month-old C57BL/6J male mice to cold (4 °C) and normal (23 °C) temperatures for 28 days and studied the effects of cold exposure on bone mass. Micro-computed tomography studies showed that the bone volume fraction was significantly reduced after 14 days of exposure to cold temperature. However, the same was recovered after 28 days. Ploton silver staining and immunohistochemical studies further revealed that exposure to cold decreased the canalicular length, number of E11- and MMP13-positive osteocytes after 14 days, but they returned to the baseline levels after 28 days unlike in the normal temperature control group. In addition, changes in Caspase-3 levels and osteocyte population indicated that exposure to cold temperature augmented apoptosis of osteocytes, while the same declined post 14 days and 28 days, respectively, conceivably affecting the bone mass directly. In vitro results confirmed the positive effect of brown adipocytes on osteocytes’ dendrites and E11 expression level. In conclusion, our findings indicate that exposure to cold temperature can influence bone mass in a time-dependent manner, with bone mass decreasing and recovering at 2 and 4 weeks, respectively. This fluctuation in bone mass may be evident due to the apoptosis and consequent decline of osteocytes.